2020
DOI: 10.1002/mrm.28297
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the snake antenna array: Geometry optimization of a sinusoidal dipole antenna for 10.5T body imaging with lower peak SAR

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Recently a passive feeding network and a snake type antenna structure were suggested to reduce peak 10 g SAR by Zivkovic et al [ 50 ] and Steensma et al [ 51 ], respectively. In future work, we will evaluate and compare SAR and SAR efficiency as a transceiver with these newly suggested techniques and we will also extend the comparison towards transmit-only and receive-only (TORO) arrays [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently a passive feeding network and a snake type antenna structure were suggested to reduce peak 10 g SAR by Zivkovic et al [ 50 ] and Steensma et al [ 51 ], respectively. In future work, we will evaluate and compare SAR and SAR efficiency as a transceiver with these newly suggested techniques and we will also extend the comparison towards transmit-only and receive-only (TORO) arrays [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RF coil is crucial for patient safety and optimal image quality. Therefore, it will be interesting to observe in future studies how promising new coil concepts which have been tested successfully in large [53,54] and in other pilot studies [55][56][57][58] will further improve the image quality in clinical imaging. Additionally, the use of automated segmentation methods based on transfer learning might add to the application of CMR at 7T [59,60].…”
Section: Plos Onementioning
confidence: 99%
“…Nevertheless, it is shown that multichannel transmit arrays (TxArrays) with improved RF performance can be used to alleviate both issues when optimal excitation strategies are used. 9,10 In the literature, various types of the transmitting elements, such as loop coils, [11][12][13][14][15][16] transmission lines, 6,9,[17][18][19] and dipole-like structures, [20][21][22][23][24][25][26] are investigated for UHF-MRI. Thalhammer et al 11 used TxArray of loop coils for cardiac imaging at 7T.…”
Section: Introductionmentioning
confidence: 99%
“…Raaijmaker et al 20,21 introduced single-side adapted and fractionated dipole as new transmitter elements for body imaging at 7T. Steensma et al 22,23 improved the SAR performance of the dipoles at 7T and 10.5T by introducing the snake antenna. Vaughan et al 6 used a TEM coil for the head imaging at 9.4T.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation